Interpersonal Communication as a Means of Self-Acceptance among People Living with HIV/AIDS in the Peer Support Group of the Intermedika Prana Foundation - Afdaliza; Mike Indarsih; Jose Fernando Sebayang (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to analyze the patterns of interpersonal communication applied by peer supporters at the Intermedika Prana Foundation in assisting people living with HIV/AIDS (PLWHA) in developing self-acceptance, as well as how such communication contributes to improving their quality of life. The research employed a descriptive qualitative method using interviews and direct observation. The informants consisted of peer supporters, foundation administrators, and PLWHA who are members of peer support groups. The findings indicate that effective interpersonal communication characterized by empathy, openness, and support plays a crucial role in helping PLWHA accept their health status. Assistance is provided on an individual basis to accommodate the diverse needs of PLWHA, with the aim of strengthening mental resilience and readiness to undergo treatment. In addition, communication conducted through a humanistic approach is able to reduce fear and rejection and increase adherence to antiretroviral therapy (ART). Thus, social support delivered through effective interpersonal communication contributes to enhancing self-acceptance among PLWHA, reducing stigma, and strengthening their commitment to treatment, which ultimately improves their quality of life.